“La oscuridad que encierra el término terrorista: una cuestión aún por definir” - Casas Rodríguez, Zulma Lucero; Ramírez Galeano, Maryuri; Caro Rivera, Anna María (Uptc, 2012)
In this article we analyze the term terrorism from its legal implication, versus the statements offered by the